UPAYA KAMPUNG BERUMBUNG BARU MEWUJUDKAN GOOD GOVERNANCE DI KEAMATAN DAYUN KABUPATEN SIAK - Sigit Pramono; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Good governance is a governance that comes from participation in which managed by people through democratic institutions that are legitimate, accountable and transparent and are used responsively for the benefit of the community. Too realize good governance in Dayun District Siak Regency, The efforts of Berumbung Baru first attempt to evaluate the level of governance, territory and society through instrument village development in accordance with the mandate of the minister of Home Affairs Regulation Number 81 of 2015 concerning Evaluation of Village Development. Evaluation of village development can be identified in village competitions helds annually by the ministry of Home Affairs the Republic of Indonesia through the Directorate General of Village Government Development. The theoretical concept used in this study is the Principle of good governance according to Santoso in which explains that the ideal concept of good governance is good governance derived from the principles of participation, accountability, transparancy and responsiveness for the benefit of the community. This study aims to find out about the efforts of Berumbung Baru Village realizing good governance in Dayun District, Siak Regency. This study uses qualitative research methods and descriptive assessment of the data. Data collection techniques are using interview, observation and documentation techniques that involve informants as the source of information. The result showed that the efforts of Kampung Berumbung Baru for realizing good governance had been maximized. This can be seen from the various achievements achieved by Berumbung Baru Village both at the Village and National levels and the National level with the crowning of the Berumbung Baru Village as the labsite location for the model of village and sub-district development throughout Indonesia. Success factors for Berumbung Baru Village realizing good governance include the leadership of the Village Head and the Potential of Berumbung Baru Village.  Keywords: Good governance, principle good governance, labsite